PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI GOTONG ROYONG - Arista Fathurrohmah; Desi Eka Pratiwi; Edi Santoso (JIP: Jurnal Ilmu Pendidikan, 2025)
This classroom action research aims to improve the learning outcomes of students on the material of mutual cooperation through the role-playing method conducted at SDN Dukuh Kupang 1-488 Surabaya in the second semester of the 2024-2025 academic year, over two cycles with each meeting consisting of 2 x 35 minutes (2 lesson hours) applying the role-playing method. The background of this research is that sixth-grade students participate in the learning activities along with the teacher, yet they struggle to instill an understanding of the implementation of mutual cooperation in their surrounding environment, namely family, school, and community. Therefore, the subject matter that should be an alternative to provide understanding of examples of mutual cooperation implementation and the benefits of its application is not conveyed well. The type of research used is classroom action research (CAR). Classroom action research (CAR) is utilized by teachers as a means of evaluating learning as well as reflecting on teachers' performance in teaching. Data on improvements in learning outcomes show that starting from the pre-cycle with a completeness percentage of 42.31% with an average score of 69.55, there is an increase in cycle I reaching 73.08% with an average score of 76.55%, and finally an improvement in learning indicated by 88.46% with an average score of 89.5. The implication of the role-playing method in this learning also indicates an increase in learning engagement and creativity of both students and teachers during the learning process.